Child Upbringing at School: The Socio-Pedagogical Aspect - Juodaitytė, Audronė (Acta Paedagogica Vilnensia, 1997)
The reform of education and the its basic documents (Common Syllabi for Lithuanian Schools of General Education, project, V., 1994) defined the educational conception "school life". In includes the relationship between teachers and students and the atmosphere of these relations which may pave the way to their normal social existence. School life and the process of child upbringing in it is based upon the possibility of the social development of the child in the sociocultural environment of a school. The life of a child at school may be evaluated as a phenomenon of his sociocultural evolution that reflects the holistic attitude of the person and his growth and maturity. It is connected with the entire environment in which the child lives (family, local community, etc.). The results of our research in the period 1991-1994 showed that the possibilities of children's social adaptation are sometimes ignored, especially in the transitional periods (for example, by passing from primary school to secondary school. In this period children's knowledge and skills get worse and children begin to distrust themselves and their teachers.
Keywords: school; upbringing; school life; cultural environment; relationship